Costa Rica : Technical Assistance Report-Revenue Administration Gap Analysis Program-Tax Gap Analysis for General Sales and Corporate Income Tax. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance Report presents the estimates of tax gaps for general sales tax (GST) and corporate income tax in Costa Rica. The estimated GST compliance gap in Costa Rica increased from 29 percent in 2012 to 31 percent in 2016. The compliance gap in 2016 was equivalent to 1.9 percent of GDP. The estimated compliance gap is higher than the average value-added tax compliance gaps of European countries and Latin American countries. Large GST compliance gaps relative to GDP are observed in manufacturing, trade, and hotels and restaurants. The estimated GST policy gaps were at about 4 percent of GDP from 2012 to 2016. Most of the GST policy gap consists of the GST expenditure gap, showing the effects of policy choices.